MicroRNAs em Solanum lycopersicum e Solanum pennellii: maquinaria de processamento, predição, validação e genes alvos - Cardoso, Thaís Cunha de Sousa (2016)
The cultivated tomato, Solanum lycopersicum, is one of the most important vegetable crops in global food and, next to the wild tomato Solanum pennelli, are species widely used in developing better cultivars. The study of the genome of plants has become a powerful tool to assist in the elucidation of the biological processes at the cellular level. One of the most important classes of small RNAs are microRNAs (miRNAs), acting on mRNA regulation in cells, inhibiting their translation and/or promoting its degradation. Computational methods have been applied extensively to identify novel miRNAs in different organisms. There are several proteins involved in the generation of miRNAs in plants, highlighting ARGONATAS proteins and DICERS proteins which have key roles in the processing machinery of miRNAs. This study aimed to search, identification, characterization and validation of genes involved in miRNA processing pathways as well as miRNAs molecules, their precursors and target genes in S. lycopersicum and S. pennellii from in silico analysis and next generation sequencing. The research methodology was based on computational analysis and sequencing for validation (small RNA-seq - NGS). We identified 65 proteins in S. lycopersicum and 109 in S. pennellii involved in small RNAs processing. Of these proteins, 23 (S. lycopersicum) and 33 (S. pennellii) miRNAs participate in the processing means. In addition, we identified 342 different mature miRNAs, 226 pre-miRNAs in 87 families, including 192 mature miRNAs not previously identified, belonging to 38 new families in S. lycopersicum. In S. pennellii we found 338 mature miRNAs, 234 pre-miRNAs contained in 85 families. All miRNAs found in S. pennellii were unpublished, being first identified in our study. From the sequencing, we validate 69 and 65 mature miRNAs distributed in 29 families and 28 in S. lycopersicum and S. pennellii respectively. Furthermore, we identified 1310 different miRNA target genes in S. lycopersicum and 2772 in S. pennellii, suggesting important roles in plant development, adaptation to stress, regulation of hormonal response, defense against pathogens and other critical processes of biology, reproduction, and marketing of these species of tomato. Thus, our results expand the study of miRNAs in plants by providing new opportunities to understand essential in regulating processes based on miRNAs in tomato.